DISTANCE LEARNING IN DEVELOPING INDONESIAN MIGRANT WORKERS’ ENGLISH-SPEAKING SKILLS OF PKBM PPI TAIWAN - Heryono, Heri; Supri, Ida Zuraida; Astarina, Atri Nadia; Hendar, Hendar; Sujatna, Meita Lukitawati (University of Kuningan, 2025)
This research explores the practices of distance learning in enhancing English speaking skills among migrant workers at the Community Learning Center (PKBM-PPI) in Taiwan. The research purpose is to understand how remote educational strategies are tailored to meet the unique needs of migrant workers, who often face challenges such as irregular work schedules and limited access to educational resources. Using a mixed-methods approach, the study combines quantitative data from pre- and post-course assessments with qualitative insights from participant interviews and instructor feedback. Key findings indicate that the integration of technology, such as mobile learning applications and online discussion forums, significantly improves learners' engagement and speaking proficiency. Additionally, the flexibility of distance learning programs allows workers to balance their educational pursuits with occupational demands. The study concludes that well-structured distance learning initiatives, supported by interactive and accessible content, can effectively develop English speaking skills among migrant workers, contributing to their personal and professional growth. The findings provide valuable insights for educators and policymakers aiming to implement effective language learning programs in similar contexts.